If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + (3x + 24) = 8 + 6x Reorder the terms: 5x + (24 + 3x) = 8 + 6x Remove parenthesis around (24 + 3x) 5x + 24 + 3x = 8 + 6x Reorder the terms: 24 + 5x + 3x = 8 + 6x Combine like terms: 5x + 3x = 8x 24 + 8x = 8 + 6x Solving 24 + 8x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 24 + 8x + -6x = 8 + 6x + -6x Combine like terms: 8x + -6x = 2x 24 + 2x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 24 + 2x = 8 + 0 24 + 2x = 8 Add '-24' to each side of the equation. 24 + -24 + 2x = 8 + -24 Combine like terms: 24 + -24 = 0 0 + 2x = 8 + -24 2x = 8 + -24 Combine like terms: 8 + -24 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 12-(3x-7)=2x-(x-1) | | -7(x+5)+3(x-6)= | | f-1(2)= | | 5-(8-x)=3-(x-6) | | -(v-2)=-4(v-8)-8v | | x(x+3)=-8 | | (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= |